High‐flow nasal oxygen for a high‐risk patient undergoing sedation in the prone position. Issue 1 (8th May 2019) - Sodha, S.; Fernandez, T.
Summary: We describe the use of high‐flow nasal oxygen for an obese patient with obstructive sleep apnoea presenting for revision of a spinal cord stimulator. The use of high‐flow nasal oxygen allowed the delivery of a high inspired oxygen concentration with humidification and improved patient comfort compared with our usual choice of device, the Hudson mask. It also provided continuous positive airways pressure which is likely to have reduced pharyngeal collapse and atelectasis. The use of high‐flow nasal oxygen enabled the delivery and careful titration of deep sedation with propofol and remifentanil, to allow a successful revision procedure to take place without airway complications or significant oxygen desaturation in a high‐risk patient in the prone position.